From Batu to Janybek: Military Conflicts of the Ulus of Jochi with Poland and Hungary (2) » - R. Hautala (Золотоордынское обозрение)
Research objective: The author of this article examines a number of military conflicts between the ulus of Jochi and both Hungary and Poland followed the first invasion of the Tatars in these lands in 1241. Research materials: For the most part, the author’s analysis is based on information of synchronous Latin sources in comparison with information contained in Russian and Mamluk chronicles. In addition to the Hungarian, Polish, and German chronicles, the author resorts to the use of the contents of the papal letters to Eastern Europe, which provide both the most reliable information about military conflicts and information on the Papal Curia’s measures to improve the defense of eastern borders of the Latin world from the Tatar raids. Research results and novelty: During the reign of Batu, Latin sources indicate extreme concern about the possible resumption of the western expansion of the Tatars in spite of the fact that, in reality, Tatar military activity on the eastern borders of Catholic Europe had an extremely minor character. On the contrary, during the reign of Berke, Tatars carried a very destructive raid on Lesser Poland. However, further Tatar expansion was interrupted by an unexpected collapse of the Mongol Empire. The subsequent reign of khan Mengu-Timur was distinguished with relative tension with the Catholic Europe. However, the actual attack on Hungary and Poland took place only under the khans Tuda-Mengu and Tula-Buga. Later, under the khans Tokhta and Uzbek, the tension between the Golden Horde and Catholic Europe weakened considerably, which, in particular, allowed the beginning of the Hungarian territorial expansion into Moldova. However, the end of the reign of khan Uzbek was characterized by a sharp deterioration of relations between the Golden Horde and Poland, which was associated with the beginning of the war of Galician succession. Analysis of the course of this war shows the apparent weakening of the influence of the Golden Horde in the former Galicia-Volyn principality, which contributed to the further expansion of Poland and Lithuania on the territory of modern Ukraine.